Effects of transcranial alternating current stimulation on motor performance and motor learning for healthy individuals: A systematic review and meta-analysis - Hu, Kun; Wan, Ruihan; Liu, Ying; Niu, Maolin; Guo, Jianrui; Guo, Feng (Frontiers in Physiology, 2022)
Objective: Previous behavioral studies reported the potential of transcranial alternating current stimulation (tACS) in analyzing the causal relationship between neural activity and behavior. However, the efficacy of tACS on motor performance and learning in healthy individuals remains unclear. This systematic review aims to examine the effectiveness of tACS on motor performance and motor learning in healthy individuals. Methods: Literature was systematically searched through the Cochrane Library, PubMed, EMBASE, and Web of Science until June 6, 2022. Eligible studies should meet randomized, parallel, or cross-over experimental design and report the efficacy of tACS on motor performance and motor learning in healthy adults. Review Manager 5.3 was used to evaluate the methodological quality and analyze the combined effect. Results: Seven studies (208 participants) met all the inclusion criteria. Results showed that the motor performance was not significantly greater than in the sham tACS stimulation [I2=4%, 95%CI (–0.04, 0.36), p=0.11, SMD=0.16], whereas motor learning ability improved significantly [I2=33%, 95%CI (−1.03, −0.31), p=0.0002, SMD=−0.67]. Subgroup analysis found that stimulation frequency did not affect the changes of motor performance, but online tACS did [I2=39%, 95% CI (0.05, 0.55), p=0.02, SMD=0.30]. Conclusions: Results showed that tACS could effectively improve motor performance (online mode only) and motor learning in healthy individuals, which indicated that tACS may be a potential therapeutic tool to improve motor behavioral outcomes. However, further evidence is needed to support these promising results.